GAMBARAN REVENGE BEDTIME PROCRASTINATION PADA MAHASISWA - Khou, Meryl Adelyn; Sahrani, Riana; Marella, Bianca (Fakultas Psikologi Universitas Tarumanagara, 2024)
Good quantity and quality of sleep contribute to a healthy sleep condition, while poor quantity and quality of sleep can be caused by revenge bedtime procrastination. Revenge bedtime procrastination is the decision to sacrifice sleep time to free up time from a busy daily schedule. In Indonesia, there is a limited amount of research on the description of revenge bedtime procrastination among students. Therefore, this study aims to explore the behavior of revenge bedtime procrastination among students. The research method applied is a descriptive method with a quantitative approach, utilizing the Bedtime procrastination Scale (BPS) as the research instrument. Based on the research results regarding revenge bedtime procrastination among students, it can be concluded that the majority of students experience a high level of bedtime procrastination (59.5%), followed by a moderate level (39.6%), and a low level (0.9%). The majority of respondents (93.8%) state that a busy daily schedule leads them to delay bedtime. This indicates a significant correlation between a hectic daily schedule and the tendency towards bedtime procrastination. The study also highlights that a significant portion of students (63.2%) delays bedtime due to involvement in specific activities. Factors such as gadget use (26.5%) and difficulty sleeping (10.3%) also make a significant contribution to delaying bedtime. The research findings reveal no significant differences in revenge bedtime procrastination based on gender, age, education level, disturbance with daily schedules, and reasons for delaying bedtime.